Unusual presentation of medication‐induced atrial fibrillation: A case report - Thamir Hashim; Yavuz Yigit; Khalid Yasir Fadul; Mostafa Dayraki; Ashraf Elmalik; Baha Hamdi Alkahlout; Aftab Mohammad (Clinical Case Reports)
Key Clinical Message This case highlights that atrial fibrillation can occur as an adverse effect of tamsulosin even in younger patients at lower doses, challenging the conventional understanding that this complication primarily affects older individuals on higher doses. Clinicians should remain vigilant for this potential side effect across all patient demographics to ensure prompt identification and management.